La figura del guerrero galaico-minhoto como soporte epigráfico - García Martínez, Sonia María (Estudios humanísticos. Geografía, historia y arte, 1995)
The image of the Galizian warrior not only constitutes the most important expression of the hispanic art of the forts in the north-west, but it is also used as an epigraphic support during the Roman period. The present paper will deal with this subject, basing our opinions on the five monuments with Latin text in the peninsular north-west.